Synthesis, Characterization, and Biological Properties of Cr(III), Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) Complexes Derived from 1,3-Oxazol-5-(4H)-One - Al-Hassani, Rehab Abdul Mahdi; Mohamed, Sinan Midhat; Rasheed , Anaam Majeed; Maryoosh, Asmaa Abdul Baqi; Hussein , Ali Abdul Rasool (Iraqi Journal of Science, 2022)
New 1,3-oxazol-5(4H)-one(3) was synthesized by cyclization of[(4-Methyl phenyl-carbonyl)amino]acetic acid (2). The starting materials were readily obtained by acylation of 2-amino acetic acid (Glycine) with 4-methyl phenyl chloride .Imidazole(4) was synthesized by reaction of compound (3) with hydrazine hydrate (99%). Compound (4) was isolated and characterized by 1HNMR , FTIR , uv-vis spectroscopy and elemental analysis (C.H.N). Compound (4) has been used as a ligand (L) to prepare a number of metal complexes with Cr(III), Mn(II), Co(II), Ni(II) , Cu(II) and Zn(II).The prepared complexes were isolated and characterized by FTIR and Uv-vis spectroscopy elemental analysis (C.H.N), flame atomic absorption technique, as well as magnetic susceptibility and conductivity measurements. The biological activity of the synthesized ligand (L) and its metal complexes were screened against the bacteria (S. aureus, B.Subtilis) and fungi (C.albicans) at the minimum inhibitory concentration method. Amoxiciline drug was used for comparison under similar conditions. They showed remarkable biological activity.